Revealing the influence of zeolite and fiber on the processes of structure formation in plasticized cement compositions - Dovgan, Alexandra (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates cement-plasticized slurry for the production of decorative concrete based on it. Given the difficult operating conditions of concrete in architectural elements, it is important to enable the preservation of its functional properties. Due to the fact that the microstructure of the material of articles is a rather disordered system, consisting of substructures and discontinuities of different composition, it is necessary to optimize the process of cluster aggregate formation and its interparticle interaction. This paper considers issues related to the study of the influence of modifiers and fibers on the processes of structure formation of 25 pastes. Analysis of changes in rheological parameters revealed that, depending on the composition of discrete particles and their modification, it is possible to significantly improve the adhesion strength and energy of the interaction of aggregates. It was found that when replacing part of the cement with zeolite in highly plasticized unreinforced systems, the plastic strength increases by 11.5 times, and the rate of its growth at the point of 2 kPa increases by 1.7 times. It was established that among discrete fibers, short fibers have a significant impact on the initial process of structure formation of pastes, especially in compositions with a low level of modification of binder systems. An increase in the content of short fibers while simultaneously reducing long fibers provides an increase in plastic strength and speed by 4.2 and 3.3 times, respectively. The use of kinetic equations of structure formation processes together with experimental and statistical models for analyzing the influence of formulation factors on rheological indicators is appropriate in the design of rational compositions of binder slurry for decorative concretes. The devised compositions of cement slurry, subject to comprehensive analysis and optimization of the parameters of the structure of the binder stone, will be implemented in the practice of manufacturing concrete for architectural elements